How Corporate Influence Continues to Undermine the Public’s Health - Soskolne, Colin L.; Baur, Xaver (European Journal of Oncology and Environmental Health, 2019)
Objectivity requires the minimization and control of potential biases in the design and interpretation of scientific studies conducted to investigate linkages between exposures and outcomes. Unless the objectivity of science can be assured, the ability of science to advance knowledge in the pursuit of truth will be undermined. While several types of bias are typically controlled at the design stage of a scientific study, the role of influence from any of a number of sources, and with different motivations and intent, is only more recently being recognized for its role in derailing science. This negative influence not only affects the course of science in advancing knowledge, but also in delaying the ability of science to inform policy to prevent ill-effects and achieve justice for potential harms arising from delays caused through the casting of doubt about evidence. The greatest bias of this type comes from those with a vested interest in the outcome, most typically financially driven. To exemplify the problem in occupational and environmental health, we organized a scientific session at the Ramazzini Days in November 2018 entitled Corporate Influence Threatens the Public Health; the abstracts of the papers presented in this session appear on pages 121 of this issue.